2011
DOI: 10.1255/jnirs.955
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Band Assignments in near Infrared Spectra of Wood and Wood Components

Abstract: Near infrared (NIR) spectra of wood and wood products contain information regarding their chemical composition and molecular structure. Both influence physical properties and performance, however, at present, this information is under-utilised in research and industry. Presently NIR spectroscopy is mainly used following the explorative approach, by which the contents of chemical components and physico-chemical as well as mechanical properties of the samples of interest are determined by applying multivariate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
495
0
35

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(554 citation statements)
references
References 106 publications
(155 reference statements)
24
495
0
35
Order By: Relevance
“…Bruker Optics OPUS 7.0 software was used for spectra collection, pre-processing, and data mining. Spectra interpretation was performed according to Schwanninger et al (2011). The list of assigned bands is summarized in Table 2.…”
Section: Ft-nir Measurementmentioning
confidence: 99%
“…Bruker Optics OPUS 7.0 software was used for spectra collection, pre-processing, and data mining. Spectra interpretation was performed according to Schwanninger et al (2011). The list of assigned bands is summarized in Table 2.…”
Section: Ft-nir Measurementmentioning
confidence: 99%
“…Near-infrared spectroscopy and X-ray photoelectron spectroscopy have been widely used for the investigation of the surface chemical composition, providing information regarding the chemical composition and molecular structure of wood (Schwanninger et al 2011;Muñiz et al 2013). Mitsui et al (2008) studied the variation of the molecular structure of heat-treated wood using NIR spectroscopy and found that the hydroxyl groups in the cellulose became degraded in the following order: amorphous, semi-crystalline, and crystalline regions.…”
Section: Introductionmentioning
confidence: 99%
“…All spectra showed several absorption band peaks in the wavelength region of 1000 nm to 1650 nm, including 1195 nm and 1462 nm. The absorbance near 1195 nm was bound up with the second overtone of C-H stretching vibration from lignin or cellulose (Schwanninger et al 2011). The strong peak at approximately 1462 nm was primarily attributed to the O-H stretching from water or phenolic groups of lignin (Schwanninger et al 2011;Yang et al 2015).…”
Section: Overview Of Spectramentioning
confidence: 99%
“…The peak at 1409 nm is due to the first overtone of O-H stretching vibration, which is attributed to phenolic groups of lignin, while that at 1586 nm is bound up with the first overtone of O-H stretching vibration from cellulose (Schwanninger et al 2011). Knots generally contain a high percentage of compression wood, which has a relatively high content of lignin and low content of cellulose .…”
Section: Fig 2 Selection Probability Of Each Wavelengthmentioning
confidence: 99%